The importance of landscape characteristics for the delivery of cultural ecosystem services - Ridding, Lucy E.; Redhead, John W.; Oliver, Tom H.; Schmucki, Reto; McGinlay, James; Graves, Anil; Morris, Joe; Bradbury, Richard B.; King, Helen P.; Bullock, James M. (Elsevier, 2017)
The importance of Cultural Ecosystem Services (CES) to human wellbeing is widely recognised. However, quantifying these non-material benefits is challenging and consequently they are often not assessed. Mapping approaches are increasingly being used to understand the spatial distribution of different CES and how this relates to landscape characteristics. This study uses an online Public Participation Geographic Information System (PPGIS) to elicit information on outdoor locations important to respondents in Wiltshire, a dynamic lowland landscape in southern England. We analysed these locations in a GIS with spatial datasets representing potential influential factors, including protected areas, land use, landform, and accessibility. We assess these characteristics at different spatial and visual scales for different types of cultural engagement. We find that areas that are accessible, near to urban centres, with larger views, and a high diversity of protected habitats, are important for the delivery of CES. Other characteristics including a larger area of woodland and the presence of sites of historic interest in the surrounding landscape were also influential. These findings have implications for land-use planning and the management of ecosystems, by demonstrating the benefits of high quality ecological sites near to towns. The importance of maintaining and restoring landscape features, such as woodlands, to enhance the delivery of CES were also highlighted.
Keywords: Cultural ecosystem services; Public participatory GIS (PPGIS); Viewshed; Landscape; Protected areas; Spatial